TRENDS IN INTRAVITREAL CORTICOSTEROID AGENT USE BY US OPHTHALMOLOGISTS IN MEDICARE BENEFICIARIES AND ASSOCIATION WITH PHYSICIAN–INDUSTRY INTERACTIONS. Issue 8 (August 2021) - Watane, Arjun; Kalavar, Meghana; Yannuzzi, Nicolas A.; Kuriyan, Ajay E.; Sridhar, Jayanth
Abstract : Purpose: To report trends of intravitreal corticosteroid use and explore the relationship between career experience, reported industry payments, and prescribing habits. Methods: A retrospective review of ophthalmologists who administered intravitreal dexamethasone implants (DEX) and triamcinolone acetonide (TA) injections between August 2013 and December 2017. Results: A total of 1, 070 US ophthalmologists were reimbursed by Medicare for 522, 804 DEX injections and 2.6 million TA injections. There was a significant positive trend in the number of DEX ( P = 0.01), but not TA, injections per year. Mid-career and late-career physicians performed significantly greater total injections on average compared with early-career physicians (both P < 0.001). Early-career physicians performed a greater proportion of DEX injections than late-career physicians ( P = 0.006). Industry payments were positively associated with the proportion of DEX used and inversely correlated with the proportion of TA administered ( P < 0.001). On multivariate analysis, years in practice, number of payments, and total value of payments were significantly associated with the number of DEX injections administered (all P < 0.001). Conclusion: From 2013 to 2017, the use of DEX increased, whereas TA use remained stable. There was a positive association between DEX use and physician–industry interactions, which may be explained by seniority and experience. This study does not define a causal relationship. Abstract : Over 5 years, the use of intravitreal dexamethasone increased consistently, whereas the use of triamcinolone acetonide injections remained stable. The use of dexamethasone use was also positively associated with ophthalmologist's career experience and payments made by industry.